Predictors of non-primary auditory and vestibular symptom persistence following surgical repair of superior canal dehiscence syndrome - Benchetrit, Liliya; Shave, Samantha; Garcia, Alejandro; Chung, Janice J.; Suresh, Krish; Lee, Daniel J. (Frontiers in Neurology, 2024)
Objective: Patients with superior canal dehiscence syndrome (SCDS) can present with a plethora of auditory and/or vestibular symptoms. While surgical repair is safe and effective, the degree of clinical improvement can vary. This study aims to assess and identify predictors of symptom persistence following repair. Setting: Tertiary neurotology single-institution care center Main outcome measures: The primary outcome was the proportion of resolved and persistent primary (most bothersome) and non-primary symptoms following SCD repair. Secondary outcomes included comparison of operative and radiologic characteristics between patients with resolved versus persistent symptoms. Standardized questionnaires including 11 auditory and 8 vestibular symptoms were administered to patients at their pre- and postoperative visits. Survey results, demographic/clinical characteristics, operative characteristics, audiometric data and cervical vestibular evoked myogenic potential (cVEMP) thresholds were compared via univariate χ 2 and multivariate binary logistic regression analyses between those reporting full resolution of symptoms and persistence of one or more symptoms. Computed tomography (CT) measurements of defect size and location were also compared. Results: Of 126 patients (132 ears) included in our study, 119 patients (90.2%) reported postoperative resolution (n=82, 62.1%) or improvement (n=37, 28.0%) of primary (most bothersome) symptoms, while 13 patients (9.8%) reported primary symptom persistence. The median (interquartile range) and range between surgery and questionnaire completion were 9 (4-28), 1-124 months, respectively. Analyzing all symptoms, 69 (52.3%) and 68 (51.1%) patients reported complete postoperative auditory and vestibular symptom resolution, respectively. The most likely persistent symptoms included imbalance (33/65/67, 50.8%), positional dizziness (7/20, 35.0%) and oscillopsia (44/15, 26.7%). Factors associated with persistent auditory symptoms included history of seizures (0% vs. 7.6%, p=0.023), higher PTA (mean 19.6 vs. 25.1 dB, p=.043) and higher cervical vestibular evoked myogenic potential (cVEMP) thresholds at 1000Hz (mean 66.5 vs. 71.4, p=0.033). Migraine history (14.0% vs. 41.9% p< 0.010), bilateral radiologic SCD (17.5% vs. 38.1%, p=0.034) and revision cases (0.0% vs. 14.0%, p=0.002) were associated with persistent vestibular symptoms. Conclusions: The persistence of mostly non-primary, symptoms and the identification of potential associated factors including migraines, PTA thresholds, cVEMP threshold, bilateral SCD and revision cases emphasize the importance of individualized patient management strategies.